2008
DOI: 10.1093/humrep/den185
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian hormone is increased in follicular fluid from unstimulated ovaries in women with polycystic ovary syndrome

Abstract: Highly elevated AMH in follicular fluid from PCOS patients in contrast to age-matched normal controls suggests that increased circulating concentrations of AMH are partly due to the increased production of AMH by individual follicles and not simply attributable to the increased number of small antral follicles. This suggests an intrinsic abnormality in the ovarian follicles themselves in PCOS, which could contribute to disordered folliculogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 27 publications
1
59
1
7
Order By: Relevance
“…3). Similarly, concentrations of AMH were found to be five times higher in follicular fluid from unstimulated follicles from women with anovulatory PCOS compared to women who were ovulatory (Das et al 2008). In a further study, the serum concentration of AMH correlated with the severity of symptoms, with again the ovulatory group having lower concentrations than those who were equally hyperandrogenic but anovulatory (Piouka et al 2009).…”
Section: Amh and Pcosmentioning
confidence: 81%
“…3). Similarly, concentrations of AMH were found to be five times higher in follicular fluid from unstimulated follicles from women with anovulatory PCOS compared to women who were ovulatory (Das et al 2008). In a further study, the serum concentration of AMH correlated with the severity of symptoms, with again the ovulatory group having lower concentrations than those who were equally hyperandrogenic but anovulatory (Piouka et al 2009).…”
Section: Amh and Pcosmentioning
confidence: 81%
“…However, the recent studies observed that the increase in AMH concentrations was more due to the increase in production of AMH by each follicle. Indeed, concentrations of AMH were found to be five times higher in follicular fluid from unstimulated follicles in women with PCOS than normoovulatory controls [7].…”
mentioning
confidence: 93%
“…This phenomenon might be the result of an intrinsic abnormality in the ovarian follicles of patients with PCOS, which could contribute to disordered folliculogenesis [20].…”
Section: Introductionmentioning
confidence: 99%